Women’s Access to Justice in Bangladesh: Constraints and Way Forward - Begum, Ajnin; Saha, Nirmal Kumar (Journal of Malaysian and Comparative Law, 2017)
Bangladesh’s prevailing justice system is viewed by many as gender biased, anti-poor and exclusionary. Accessibility to the justice system is one of the most important strategies for legal empowerment for women. Legal, social, institutional, economic constraints such as inadequate legal framework, institutional barriers, lack of legal awareness, gender discrimination and poverty are the main barriers that women in Bangladesh face in obtaining access to justice. Securing access to justice for women requires comprehensive strategies and action plans to address the constraints mentioned above. It also involves a complex combination of legal and institutional reforms so that justice system can reach women in rural areas. In order to make the Bangladeshi justice system more accessible for women and legal empowerment for women operational, collaboration and coordinated efforts are needed by a host of legal actors from pro bono lawyers, activist judiciary, to NGOs.